Comparing the economic burden of disease by physical activity levels among persons with and without disabilities in the Republic of Korea - Lee, SeungCheor; Oh, Chang-Mo; Jung, Young-il; Park, So-Youn; Oh, In-Hwan (Frontiers in Public Health, 2024)
IntroductionThe World Health Organization recommends at least 150 min of physical activity per week for persons with and without disabilities. This study compared the differences in the economic burden of diseases between persons with and without disabilities based on their physical activity. What is known in the field is that physical activity is beneficial to health, but there is a disparity between persons without disabilities and persons with disabilities, and our research aims to increase physical activity among persons with disabilities.MethodsEconomic burden of disease includes service costs such as outpatient, hospitalization, and pharmaceutical expenses for disease treatment, and persons with disabilities are those who have received a disability classification legally registered by the Korean Ministry of Health and Welfare, and there are 15 types of disabilities. For exercise records, we calculated the cost in 2020 for people with exercise records in 2018 so that they can have at least 1 year of exercise records, as health checkups are available from January to December of the year. Physical activity attainment is defined as 150 min or more of physical activity per week based on World Health Organization guidelines.ResultsCalculating the economic burden of disease by physical activity for persons with and without disabilities, both experienced a difference in hospitalization costs owing to fewer hospital days with physical activity achievement, with the difference being greater for persons with disabilities. Regarding disability type, achievers showed a 41.1% difference in total costs for mental class disorders, 16.7% for external bodily function disorders, and 11.1% for internal organ disorders.DiscussionPhysical inactivity has a significant impact on the economic burden of persons with disabilities compared to persons without disabilities, with 11.8% fewer persons without disabilities who were physically active for 150 min or more per week compared to 21.4% fewer persons with disabilities. In terms of healthcare spending, exercise can help keep persons with disabilities healthy. Therefore, there is a need for exercise programs tailored to persons with disabilities to increase physical activity in line with World Health Organization recommendations to reduce health inequalities between persons with and without disabilities.